Recreational services in the city of Baghdad (Baghdad Tourist Island) (Journal of the College of Basic Education, 2024)
Recreational services are one of the important services in cities as they represent the only outlet in the city, especially the river islands because of their privileged location, as they are surrounded by water from all sides, which gives them a special moderate environment, as well as the beauty of the area because it is surrounded by gardens, as water with plants gives the area a natural aesthetic characteristic that gives hikers reassurance and psychological comfort. Note that the tourist island of Baghdad suffers from a lack of efficiency in the services provided, whether food, drink and sanitation services, as well as the inefficiency of games and their high prices, as for the gardens, there are no places to sit, especially the holiday season, events and school trips, so the responsible authorities should pay attention to the island as it represents an important park for the residents of the city of Baghdad